Why isn’t the recent inflation related to real variables, such as unemployment and output? - Hukkinen, Juhana; Viren, Matti (SUERF - The European Money and Finance Forum, 2026)
Recent inflation does not seem to correspond to the textbook illustration of inflation, in the sense that it is very hard to detect a Phillips curve relationship between inflation and real variables, such as unemployment and output. Until recently, the time paths of these real variables have been almost constant, suggesting that in order to explain inflation developments, there should have been significant shifts in the slopes of the Phillips curve. That might be the case, but the puzzling feature is that the relationships have become weak, and the explanatory power of time series empirical models is very low. This is not limited to the 2021-2023 period. In this environment, it is difficult to assess how policy actions have contributed to the surge of inflation and similarly to the recent downfall of inflation.